2018
DOI: 10.1038/s41598-018-25736-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Circulating PBMCs to Understand Mechanism of High Altitude Adaptation in Native Cattle of Ladakh Region

Abstract: Ladakhi cattle is native population of Leh and Ladakh region and constantly exposed to hypobaric hypoxia over many generations. In present study, transcriptome signatures of cattle from Ladakh region (~5500 m) and Sahiwal cattle from tropical regions were evaluated using Agilent 44 K microarray chip. The top up-regulated genes in Ladakhi cows were INHBC, ITPRI, HECA, ABI3, GPR171, and HIF-1α involved in hypoxia and stress response. In Sahiwal cows, the top up-regulated genes eEF1A1, GRO1, CXCL2, DEFB3 and BOLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 55 publications
(45 reference statements)
1
29
0
Order By: Relevance
“…They did not find associations between variants of these candidate genes and the susceptibility to HAPH, but a follow‐up microarray analysis did reveal biologically relevant pathways involved in HAPH susceptibility by expression profiling of peripheral blood mononuclear cells (Newman et al ). A further transcriptome study of peripheral blood mononuclear cells of native Indian cattle revealed greater expression of the HIF‐1 , EPAS1 , VEGFA , NOS2 , and GLUT1/SLC2A1 genes in cattle from high altitude compared with low‐altitude individuals (Verma et al ). Other comparative transcriptome studies between cattle and yak revealed that, among several organs, gene expression patterns of the heart showed the greatest differentiation between the two species (Wang et al ) and that differentially expressed genes in lung and gluteus tissue are involved in red blood cell development and the inhibition of blood coagulation (Xin et al ).…”
Section: Genetic Background Of High‐altitude Adaptationmentioning
confidence: 99%
“…They did not find associations between variants of these candidate genes and the susceptibility to HAPH, but a follow‐up microarray analysis did reveal biologically relevant pathways involved in HAPH susceptibility by expression profiling of peripheral blood mononuclear cells (Newman et al ). A further transcriptome study of peripheral blood mononuclear cells of native Indian cattle revealed greater expression of the HIF‐1 , EPAS1 , VEGFA , NOS2 , and GLUT1/SLC2A1 genes in cattle from high altitude compared with low‐altitude individuals (Verma et al ). Other comparative transcriptome studies between cattle and yak revealed that, among several organs, gene expression patterns of the heart showed the greatest differentiation between the two species (Wang et al ) and that differentially expressed genes in lung and gluteus tissue are involved in red blood cell development and the inhibition of blood coagulation (Xin et al ).…”
Section: Genetic Background Of High‐altitude Adaptationmentioning
confidence: 99%
“…The EPAS1/HIF-2α which is a transcription factor that belong to hypoxia-inducible factor signaling pathway was found to be involved high altitude adaptation in through its role in response to hypoxia, erythropoiesis, iron homeostasis, pulmonary hypertension 1,11,[14][15][16] . ITPR1 gene is target of HIF-2α and is involved in high altitude adaptation mechanisms 12 . HIF-1α regulates the oxygen homeostasis in cells and also regulates glycolysis 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…NOS2 gene is expressed during the high altitude hypoxia and may aid in improved pulmonary capacity in high altitude 19 . GLUT1 like glucose transporters are responsible for anaerobic metabolism 12 . The SNPs identified in the candidate genes for high altitude adaptation need to be explored further in large population for its role in the adaptation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations